2014
DOI: 10.1557/opl.2014.898
|View full text |Cite
|
Sign up to set email alerts
|

MAPbI3-xClx mixed halide perovskite for hybrid solar cells: the role of chloride as dopant on the transport and structural properties

Abstract: Hybrid halide perovskites represent one of the most promising solutions toward the fabrication of all solid nanostructured solar cells with improved efficiency and long-term stability. This article aims at investigating the structural properties of the iodide/chloride mixed-halide perovskites and correlating them with the photovoltaic performances of the related sensitized solar cells. We found out that, independently on the components ratio in the precursor solution, Cl incorporation, in a I-based structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
226
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(257 citation statements)
references
References 15 publications
29
226
0
2
Order By: Relevance
“…Note that Cl-doping is a common technique for achieving higher open circuit voltage and long diffusion lengths of perovskite solar cells [23][24][25]. Despite intensive studies to increase the Cl content, the control of the Cl content in perovskite is extremely difficult, resulting in the negligible content of Cl in perovskites [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that Cl-doping is a common technique for achieving higher open circuit voltage and long diffusion lengths of perovskite solar cells [23][24][25]. Despite intensive studies to increase the Cl content, the control of the Cl content in perovskite is extremely difficult, resulting in the negligible content of Cl in perovskites [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…First, it is found that the chloride was absent at the GBs for both smaller and larger grain perovskites, which provides a critical insight into the nature of grain boundaries. This is because the presence of Cl in MAPbI 3 plays a critical role in mitigating the formation of defects, but yielding a long diffusion length of charge carriers in perovskites [23][24][25]. The absence of Cl at the GBs suggests that the GBs are more defective and yield shorter diffusion lengths of charge carriers when compared with the GIs.…”
Section: Resultsmentioning
confidence: 99%
“…As far, the most successful perovskites MAPbI 3 , with a bandgap of 1.55 eV [44][45][46][47], correspond to an efficiency up-limit of 31.3%, and FAPbI 3 with a more favorable bandgap of 1.47 eV [47][48][49] could result in a higher efficiency up-limit of 32.5%.…”
Section: Tunable Bandgapsmentioning
confidence: 99%
“…Yet the intrinsic role of Cl  dopant in the MAPbI 3x Cl x film is still under debate [64][65][66][67]. The dissenters thought the difference in ionic radii between Cl  and I  was too large for the cubic perovskite crystal structure to provide any doping tolerance for Cl  [45]. Besides, the amount of the residue Cl  ions in the MAPbI 3x Cl x film and their exact location in the crystal domains are also not clear.…”
Section: Charge Transportmentioning
confidence: 99%
“…S3) implied a homogeneous distribution of Cl in the MAPbI 3-x Cl x perovskite films. claimed that Cl incorporation in a iodide-based structure is reasonable but only at a relatively low concentration levels [29,30]. However, the positive-shift of the MAPbI 3-x Cl x (110) and…”
Section: Resultsmentioning
confidence: 99%